Interdisciplinary Studies in Higher Education; Student Centered Summer Schools of “YTU–BEST” - Vural, Müjdem S. (Elsevier, 2012)
Today in higher education, students are one of the pioneers of new responsibility shareholders formed by the reflection of globalization. As one of the responsibilities to increase the awareness on education issues and to gain knowledge through experience, students constructed an organization “Board of European Students of Technology (BEST)”. Throughout Europe, BEST supports interdisciplinary studies since 1989. Three summer schools of Yildiz Technical University BEST will be discussed in the sense of interdisciplinary study examples to evaluate the contributions of student centred education on student’ s individual and collective learning styles, participatory design techniques and practices.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication
Keywords: interdisciplinary study; observation and freehand drawings